THE IMPORTANCE OF MEDIA EDUCATION IN THE FORMATION OF MEDIA CULTURE IN YOUTH - Тurgunov Azim Turgunovich (Western European Studies, 2023)
This article examines the process of forming a media culture, which will be a system of the level of development of a person's personality, capable not only of perceiving and assimilating new knowledge in the field of media, but also of analyzing and evaluating them.
Keywords: Media; culture; youth